Novel synthetic approach for designing metal-free, redox-active quinoxaline-benzimidazole-based organic polymers with high energy storage capacity - Salunkhe, Pravin S.; Patil, Yuvraj S.; Dhole, Indrajeet A.; Kalshetti, Basavraj S.; Patil, Vikas B.; Mane, Shivshankar R.; Ghanwat, Anil A. (New Journal of Chemistry, 2019)
New organic framework materials, namely, polyphenylquinoxaline (QOP) and polyphenylquinoxaline-benzimidazole (QOP-BOP) were designed using a high-temperature (>100 degrees C) polymerization reaction with different monomers, i.e., 2,5-bis-[(4-benzoylcarbonyl)phenyl]-3-4 diphenyl thiophene (BbcPDT), aromatic tetraamines and biphenyl dicarboxylic acid. The QOP-BOP copolymer exhibited specific capacitance (SC) of 305 F g(-1) at the current density of 2 A g(-1) and 88% retention of its initial specific capacitance after 1000 cycles, which resulted in good cyclic stability. This work establishes the first use of thiophene integrated with quinoxaline-benzimidazole units for energy storage applications and provides strategies for further developments in the performance of such conjugated materials. Cyclic voltammetry, charge-discharge and electrochemical impedance techniques were used to evaluate the electrochemical parameters, which demonstrated their potential in future energy storage devices.